Answer:
2. x = (y - 1)² + 4
Explanation:
Notes: The vertex form of a parabola is y = a(x - h)² + k or x = a(y - k)² + h
- (h, k) is the vertex
- p is the distance from the vertex to the focus
1)
Now input a = -1/2 and (h, k) = (9, 10) into the equation y = a(x - h)² + k
*****************************************************************************************
2)
Now input a = 1 and (h, k) = (4, 1) into the equation x = a(y - k)² + h
x = 1(y - 1)² + 4 → x = (y - 1)² + 4
*****************************************************************************************
3)
Now input a = 1/2 and (h, k) = (7, 2) into the equation x = a(y - k)² + h